Transforming Farming with Technology: A Smart Novel Agriculture Framework and Infrastructure. - Mushtaque Ahmed Rahu (Sukkur IBA Journal of Computing and Mathematical Sciences)
Smart agriculture represents a burgeoning concept revolutionizing traditional farming by seamlessly integrating crucial technologies with sensory and internet-enabled devices. This transformation is realized through the harmonious amalgamation of diverse technological components, including Wireless Sensor Networks (WSN), Internet of Things (IoT), robotics, drones, and robust computing infrastructure. Our study presents a novel framework and comprehensive infrastructure for smart agriculture, covering from sensing (physical) layer to end-user (application) layer. It includes communication technologies, IoT, WSN, autonomous vehicles, computing, and data processing. We also analyze the disparities between traditional and smart agriculture across various parameters. We conclude the paper by suggesting some recommendations, which can assist in the revolutionary change in agriculture for worldwide adoption.